Feedlot and milo stubble fattening tests with feeder lambs. Studies carried on by the Department of Animal Husbandry and the Garden City Branch Experiment Station. - Bell, T.D.; Erhart, A.B. (Kansas Agricultural Experiment Station, 2012)
The tests this year compared whole milo with steam rolled milo, and with ground milo when fed with a standard roughage ration of ground sorghum stover plus a protein supplement and supplemental salt and limestone. The roughage comparisons included: (1) all sorghum stover, (2) all alfalfa hay, (3) one-half alfalfa hay and one-half sorghum stover (with and without a protein supplement), and (4). part sorghum stover and part sorghum silage.
Keywords: Sheep; Feedlot; Milo